2023
DOI: 10.1002/cssc.202300418
|View full text |Cite
|
Sign up to set email alerts
|

Trace Ionic Liquid‐Assisted Orientational Growth of Cu2O (110) Facets Promote CO2 Electroreduction to C2 Products

Abstract: Cu 2 O has great advantages for CO 2 electroreduction to C 2 products, of which the activity and selectivity are closely related to its crystal facets. In this work, density functional theory calculation indicated that the (110) facets of Cu 2 O had a lower energy barrier for the CÀ C coupling compared to the ( 100) and ( 111) facets. Therefore, Cu 2 O(110) facets were successfully synthesized with the assistance of trace amounts of the ionic liquid 1-butyl-3-methylimidazolium ([Bmim]BF 4 ) by a sample wet-che… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 74 publications
0
2
0
Order By: Relevance
“…Very recently, it has been proved that the design of the Cu-based electrocatalyst, for instance by tuning the growth of specific crystallographic planes using ionic solvents, has allowed to promote the CO 2 RR to C 2 products such as ethanol and ethylene. [123] Apart from the relevance of ionic solvents in the cathodic material synthesis, they are able to stabilize ionic metallic species in solution. This is particularly relevant in the case of DES, thanks to the large amount of chloride anions present in their composition.…”
Section: Co 2 Rr In Des For the Production Of C 2 + Compoundsmentioning
confidence: 99%
“…Very recently, it has been proved that the design of the Cu-based electrocatalyst, for instance by tuning the growth of specific crystallographic planes using ionic solvents, has allowed to promote the CO 2 RR to C 2 products such as ethanol and ethylene. [123] Apart from the relevance of ionic solvents in the cathodic material synthesis, they are able to stabilize ionic metallic species in solution. This is particularly relevant in the case of DES, thanks to the large amount of chloride anions present in their composition.…”
Section: Co 2 Rr In Des For the Production Of C 2 + Compoundsmentioning
confidence: 99%
“…On the other hand, through various studies, it has been reported that another O/Cu(111) surface oxide exists, which has been proposed as a metastable state. It is referred to as the “8” structure and possesses motifs resembling the zigzag shape of Cu 2 O­(110), in contrast to the hexagonal motifs found in the other surface oxides on Cu(111) which resemble the surface geometry of Cu 2 O­(111). When considering that the Cu 2 O­(110) surface is identified to be photocatalytically active for CO 2 reduction to methanol , and has enhanced C 2 selectivity, an accurate atomic structure determination of the “8” surface oxide is important. It may also lead to additional insights concerning the advantageous active sites and mechanisms for the CO 2 reduction reaction.…”
Section: Introductionmentioning
confidence: 99%